Microwave Assisted Synthesis of BenzilideneBenzylamine and Its Acetylcholinesterase and Butyrylcholinesterase Activity - Himayat Ullah; Khair Zaman; Muhammad Ismail (Journal of Tropical Pharmacy and Chemistry, 2020)
BenzilideneBenzylamine the derivative of Schiff bases contain azomethine group already used widely for industrial purposes and have wide range of biological activities. Benzilidene Benzylamine were synthesized by microwave irradiation reacting different aromatic and aniline purified pure crystal, 85% yield obtained reaction monitor by TLC. The Anticholinesterase activity utilized spectrophotometric Ellman assay for determination of butyrylcholinesterase and acetylcholinesterase. The synthesis compound 1 – 6 showed a wide range of inhibitory activity the compound 3((E)-N-(4-fluorobenzylidene)aniline) at 1000µg/mL, 71.62±0.74 percent inhibitory acetylcholinesterase potential while compound 6 ((E)-4 ((phenylimino)methyl) benzaldehyde) at 500 and 1000 µg/mL at IC50 show 71.68±0.22, 77.84±0.32 percent inhibitory potential comparatively greater than standard Galanthamine at 62.5µg/mL, 74.10±0.90 at IC50. The butyrylcholinesterase activity of compound 6 ((E)-4 ((phenylimino)methyl)benzaldehyde) at 1000 µg/mL, show 75.83±1.07 percent inhibitory potential which is similar to standard compound at 62.5µg/mL concentration of 75.45±0.90 percent butyrylcholinesterase inhibitory activity.